Migration of Bisphenol A and Bisphenol A Diglycidyl-ether from Can Coatings into Food Simulants - Lin, Qin-Bao; Cai, Long-Fei; Wu, Shao-Jing; Chen, Zhi-Nan; Wang, Zhi-Wei (Asian Journal of Chemistry, 2015)
The migration and alteration of the key bisphenol-A-related compounds, bisphenol A and bisphenol A diglycidyl-ether, in food simulants (deionized water, 3 % acetic acid and 50 % ethanol) stored in coated cans were investigated. Quantification and confirmation of the two compounds were performed with ultrahigh-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). Recoveries for bisphenol A and bisphenol A diglycidyl-ether at three concentration levels (10, 25, 250 μg L-1) ranged from 81.8 to 101.5 % and RSDs were 2.61 to 12.52 %. The effects of the initial concentration, heat processing (for sterilization), time and temperature of storage on migration and alteration of bisphenol A and bisphenol A diglycidyl-ether were investigated. The results showed that heat processing contributed greatly to bisphenol release. Besides, storage temperature and time had a significant effect on the migration of bisphenol A , with concentrations increasing gradually with time and temperature. Conversely, the concentrations of bisphenol A diglycidyl-ether decreased during storage because of hydrolysis by the food simulants, especially for aqueous acetic acid.